Cross-cultural design : user experience of products, services, and intelligent environments : 12th International Conference, CCD 2020, Held as Part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings, Part I /: user experience of products, services, and intelligent environments : 12th International Conference, CCD 2020, Held as Part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings, Part I. ([2020]) - Unknown
No abstract available